Evaluating the efficiency of isolated calvaria bones shape changes in the identification and differentiation of artificial cranial modification techniques among pre-Hispanic western and central Mesoamerican populations. (October 2021) - Natahi, Sélim; Coquerelle, Michael; Darras, Véronique; Faugère, Brigitte; Fisher, Christopher T.; Pereira, Grégory; Bayle, Priscilla
Highlights: In Mesoamerican archaeology, the state of preservation of the bone occasionally limits the possibility of reliably diagnosing and differentiating artificial cranial modifications (ACMs). Using 3D geometric morphometrics, we quantified the shape differences of calvaria bones in isolation among four groups of individuals with distinct forms of ACMs and a control group of unmodified skulls. The shape of isolated calvaria bones can be informative for the identification and the characterization of ACM in western and central Mesoamerica. Abstract: Introduction: Artificial cranial modification (ACM) is a widespread cultural phenomenon that has been reported in human populations from Late Pleistocene to present day all over the world. Although ACM techniques have been documented in western and central Mesoamerica, the state of preservation of bone has occasionally limited the possibility of diagnosing and differentiating ACM variants. To explore how informative fragmentary skull remains can be in this matter, here we used 3D geometric morphometrics to quantify shape variation of isolated calvaria bones. Materials and Methods: 49 well preserved individuals from west and central Mesoamerica were selected and divided into five groups: four showing distinct forms of ACM, and a control group of unmodified skulls. Using medical computed tomography and laser surface scanning, we measured the 3D shape changes in three isolated calvaria bones. We calculated the morphological differences within and between groups by computing pairwise Procrustes distances for all possible combinations of individuals. Finally, we used 3D digital meshes to describe the shape changes in an ACM variant compared to the other ones and to the control group. Results: Irrespective of which bone of the calvaria is considered, the variation between the individuals showing ACM and the unmodified individuals always exceeds the variation measured within the unmodified group. Furthermore, some ACM variants can be characterized by examining certain calvaria bones in isolation. Discussion: The study of isolated calvaria bones can help to identify individuals with ACM from the background physiological variation. Our study also provides information pertaining to the techniques employed to produce certain ACM variants and we discuss the standardization of these processes.